Exploring the Risks of Copulatory Trauma in Immunocompromised NOD SCID Mice (Indian Journal of Animal Production and Management, 2024)
This report documents a sudden and fatal  case of copulatory breeding trauma in a 7-month old NOD SCID male breeder mouse. While similar  injuries in other mouse strains typically result in  recovery, the immunocompromised status of NOD  SCID mice significantly impairs their healing  abilities and heightens their susceptibility to  infections. The mouse exhibited acute lethargy,  gastrointestinal distress, and penile discharge,  leading to death within a few hours. Postmortem  examination revealed a significantly distended  bladder with hemorrhagic spots, and urine analysis  showed numerous motile sperm-like structures.  The findings indicate that copulatory trauma was  the primary cause of death, emphasizing the need  for careful monitoring and preventive measures in  breeding management, particularly for  immunocompromised strains.
Keywords: NOD SCID mouse; copulatory trauma; immunodeficient mice; breeding management